Case Report: Treatment response of SQSTM1–ALK fusion lung adenocarcinoma to multiple ALK inhibitors - Gu, Jincui; Zhang, Jing; Li, Shaoli; Lin, Ziying; Huang, Lixia; Zhou, Yanbin (Frontiers in Pharmacology, 2025)
ObjectivesThe echinoderm microtubule-associated protein-like 4 (EML4) gene and anaplastic lymphoma kinase (ALK) gene fusion is the most common ALK rearrangement in non-small-cell lung cancer (NSCLC). SQSTM1 (exon 5)–ALK (exon 20) fusion in patients with NSCLC was first identified in 2015. However, the treatment of lung adenocarcinoma patients with SQSTM1–ALK fusion has not been previously reported. In this study, we report for the first time an SQSTM1–ALK fusion in a stage-IV lung adenocarcinoma patient who had a variable response after sequential treatment with alectinib, ensartinib, lorlatinib, and brigatinib.Materials and methodsThe biopsy specimen was subjected to hematoxylin–eosin (HE) staining, immunohistochemistry (IHC), and next-generation sequencing (NGS).ResultsThe patient responded to alectinib as first-line treatment and achieved stable disease for 16 months without significant toxicity. Ensartinib appeared to have a better effect on brain metastases. As third-line therapy, lorlatinib resulted in a progression free survival (PFS) of 15 months. In addition, as fourth-line therapy, brigatinib yielded a PFS of only 2 months.ConclusionThis is the first report of a patient with SQSTM1–ALK fusion who experienced different responses after treatment with alectinib, ensartinib, lorlatinib, and brigatinib. We hope that this case provides clinical evidence to guide treatment strategies for this rare variant and further supports the individualized application of ALK-tyrosine kinase inhibitors (TKIs) in patients with non-classical fusions.